A world without Jews the Nazi imagination from persecution to genocide - Confino, Alon (Yale University Press, 2014)
Why exactly did the Nazis burn the Hebrew Bible everywhere in Germany on November 9, 1938? The perplexing event has not been adequately accounted for by historians in their large-scale assessments of how and why the Holocaust occurred.